The Selective Rat Toxicant Norbormide Blocks K(ATP) Channels in Smooth Muscle Cells But Not in Insulin-Secreting Cells - Saponara, Simona (Front Pharmacol, 2019)
Norbormide is a toxicant selective for rats to which it induces a widespread vasoconstriction. In a recent paper, we hypothesized a role of ATP-sensitive potassium (K(ATP)) channels in norbormide-induced vasoconstriction. The current study was undertaken to verify this hypothesis by comparing the effects of norbormide with those of glibenclamide, a known K(ATP) channel blocker. The whole-cell patch-clamp method was used to record K(ATP) currents in myocytes freshly isolated from the rat and mouse caudal artery and from the rat gastric fundus, as well as in insulin-secreting pancreatic beta cells (INS-1 cells). Smooth muscle contractile function was assessed on either rat caudal artery rings or gastric fundus strips. Molecular modeling and docking simulation to K(ATP) channel proteins were investigated in silico. Both norbormide (a racemic mixture of endo and exo isomers) and glibenclamide inhibited K(ATP) currents in rat and mouse caudal artery myocytes, as well as in gastric fundus smooth muscle cells. In rat INS-1 cells, only glibenclamide blocked K(ATP) channels, whereas norbormide was ineffective. The inhibitory effect of norbormide in rat caudal artery myocytes was not stereo-specific as both the endo isomers (active as vasoconstrictor) and the exo isomers (inactive as vasoconstrictor) had similar inhibitory activity. In rat caudal artery rings, norbormide-induced contraction was partially reverted by the K(ATP) channel opener pinacidil. Computational approaches indicated the SUR subunit of K(ATP) channels as the binding site for norbormide. K(ATP) channel inhibition may play a role in norbormide-induced vasoconstriction, but does not explain the species selectivity, tissue selectivity, and stereoselectivity of its constricting activity. The lack of effect in INS-1 cells suggests a potential selectivity of norbormide for smooth muscle K(ATP) channels.